Learning path : C#. - Lippert, Eric; Welch, Keith; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"C# is recognized as of the most versatile programming languages around, with a strong set of abstractions, a powerful runtime, and access to a huge amount of library and platform functionality. This Learning Path offers you a clear-cut roadmap to C# proficiency, taking you from a hands-on introduction through design patterns and best practices for writing clear, maintainable code."--Resource description page.
Beginning C# programming / with Eric Lippert -- Intermediate C# programming / with Eric Lippert -- C# best practices / [by Keith Welch] -- C# design patterns / [by Keith Welch].
Title and publication information from resource description page (Safari, viewed March 14, 2016).
Presenter, Eric Lippert, Keith Welch.
Keywords: C# (Computer program language); Electronic books